Work Engagement in South Korea: Validation of the Korean Version 9-Item Utrecht Work Engagement Scale. Issue 3 (June 2017) - Ho Kim, Won; Park, Jong Gyu; Kwon, Bora
This study aims to validate Korean versions of the 9-item Utrecht Work Engagement Scale, testing for its factor pattern validity through Exploratory Factor Analysis and Confirmatory Factor Analysis, reliability, and convergent and discriminant validity. The 9-item Utrecht Work Engagement Scale was translated according to the guidelines of the International Test Commission and tested with two Korean samples. First, the Exploratory Factor Analysis found that both two-factor and three-factor solutions were viable options with the first sample. Second, comparison validations of these two solutions were tested by confirming the dimensionality of their structures through the Confirmatory Factor Analyses with the second sample, with the conclusion that the three-factor model solution was the most parsimonious model. Finally, the three-factor model of the 9-item Utrecht Work Engagement Scale was demonstrated to have good discriminant validity and convergent validity, as well as internal consistency of its subscales.